The role of Indigenous traditional institutions in fighting against the COVID-19 pandemic in Ghana. Issue 1 (2nd January 2022) - Arkorful, Vincent Ekow
ABSTRACT: Indigenous traditional chieftaincy institutions in Ghana continue to gain recognition whilst wielding influence across socio-political divides. In this viewpoint essay, against the backdrop of the fight against the global COVID-19 pandemic, the author explores the potential roles of these institutions in fighting the pandemic. Particularly cognisant of their roles in Ghana's transition from pre-colonial, colonial, and post-colonial, through independence to a democracy and its consolidation, this article argues that the existence of the chieftaincy institutions as change agents presents a wealth of opportunity to be harnessed for pandemic control, management, and containment.